The Psychological and Social Impact of Covid-19: New Perspectives of Well-Being - Saladino, Valeria; Algeri, Davide; Auriemma, Vincenzo (Frontiers in Psychology, 2020)
The recent Covid-19 pandemic has had significant psychological and social effects on the population. Researches has highlighted the impact on psychological well-being of the most exposed groups, including children, college students and health workers, who are more likely to develop post-traumatic stress disorder, anxiety, depression and other symptoms of distress. The social distance and the security measures affected the relationship among people and their perception of empathy towards others. From this perspective, telepsychology and technological devices assume an important role to decrease the negative effect of the pandemic. These tools present benefits which could improve psychological treatment of patients online, such as the possibility to meet from home or from the workplace; saving money and time and maintaining the relationship between therapists and patients. Aim of this paper is to show empirical data from recent studies on the effect of the pandemic and reflect on possible interventions based on technological tools.